2019
DOI: 10.1002/jum.15078
|View full text |Cite
|
Sign up to set email alerts
|

Increased Stiffness of Rotator Cuff Tendons in Frozen Shoulder on Shear Wave Elastography

Abstract: Objectives-To evaluate the stiffness and morphologic characteristics of the capsule, rotator cuff tendons and muscles, coracohumeral ligament (CHL), and long head of the biceps in patients with frozen shoulder using shear wave elastography (SWE) with B-mode ultrasound.Methods-Thirty-two patients with frozen shoulder were divided into freezing and frozen phases. All patients had limitations of their range of motion without rotator cuff tears. Stiffness was measured by SWE in the supraspinatus (SSp) tendon, infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
1
25
2
Order By: Relevance
“…Other recent studies have suggested that changes in the elastic modulus of the rotator cuff tendons may also occur in adhesive capsulitis (17,31) , which we have not measured. Further studies are required to further investigate these findings in order to fully understand complex changes in the elastic properties of the rotator interval structures and rotator cuff tendons that may occur in adhesive capsulitis.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Other recent studies have suggested that changes in the elastic modulus of the rotator cuff tendons may also occur in adhesive capsulitis (17,31) , which we have not measured. Further studies are required to further investigate these findings in order to fully understand complex changes in the elastic properties of the rotator interval structures and rotator cuff tendons that may occur in adhesive capsulitis.…”
Section: Resultscontrasting
confidence: 48%
“…The ultrasound system propagates shear waves into tissues and assesses their elastic modulus. This has been used in a variety of musculoskeletal conditions including the rotator cuff tendons (16,17), epicondylitis (18) , and Achilles (19) . Wu et al reported that in patients with clinical findings consistent with adhesive capsulitis shear wave elastography demonstrated that the CHL was significantly stiffer in the symptomatic shoulder compared with the asymptomatic shoulder (13) .…”
Section: Introductionmentioning
confidence: 99%
“…15 Very recently, several studies have reported its use and proven its reproducibility for exploring ligament structures in the shoulder, knee, and lateral ankle ligaments. 20,24,53…”
Section: Introductionmentioning
confidence: 99%
“…15 Very recently, several studies have reported its use and proven its reproducibility for exploring ligament structures in the shoulder, knee, and lateral ankle ligaments. 20,24,53 The objective of this pilot study was to determine whether SWE quantifies SWS distributions and their changes with position in the deltoid ligament complex in a cohort of healthy adult volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Young's modulus is a parameter commonly used in the expression of tissue elasticity 3,4 . The elasticity of tissue is often closely related to its functional state, and the detection of Young's modulus of tissue carries important clinical significance 5–7 . Using the acoustic radiation force of focused ultrasound beams, the supersonic shear imaging (SSI) technique generates shear waves.…”
Section: Introductionmentioning
confidence: 99%